Sistem Pendukung Keputusan Pemilihan Perumahan Menggunakan Kombinasi Metode ROC dan ARAS - Ristasari Dwi Septiana; Arief Herdiansah; Ri Sabti Septarini; Muhammad Irfan (FORMAT, 2025)
Selecting a suitable house is a multifaceted process that involves several considerations, including cost, location, available facilities, security, and access to transportation. Because decisions are often made subjectively, there is a risk of inefficiency, which highlights the need for a structured decision-making approach. This study presents the development of a web-based decision support application that combines the Rank Order Centroid (ROC) method for assigning criterion weights based on their priority order, and the Additive Ratio Assessment (ARAS) method for evaluating and ranking housing alternatives based on relative utility scores. The system was implemented using PHP and MySQL, incorporating modules for managing criteria, alternatives, inputting evaluations, and generating automated calculations and visual outputs. A case study with five housing options and five main evaluation criteria was conducted. The research employed a structured methodology involving problem identification, criteria selection, weight calculation using ROC, alternative evaluation using ARAS, system development, and black-box testing for validation. The findings revealed that Taman Permata achieved the highest utility score of 0.8616, placing it as the top-ranked alternative. Functional testing through a black-box approach verified that all components operated as intended. Overall, the system offers a transparent and effective tool to support users in identifying the most appropriate housing option according to their individual needs and priorities.